Struktur Organisasi, Desain Kerja, Budaya Organisasi Dan Pengaruhnya Terhadap Produktivitas Karyawan Studi Kasus Pada PT. XX Di Jakarta - Yanti Budiasih (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2012)
The objectives of this study are to analyze changes in organizational structure, job design, organizational culture and its influence on employee productivity at PT. XX in Jakarta and to identify variables that have a dominant influence on the productivity of employees. The research method used is using multiple linear regression analysis. The results show that the all variables simultaneously and partially change the organizational structure, job design, and organizational culture has a significant impact on employee productivity at PT. XXin Jakarta.